Air dispersion modeling of SOx and NOx emissions from a petroleum refinery plant - Carrillo, Jan-Michael Y. (2003)
Dispersion modeling of SOx and NOx emissions from a petroleum refinery plant was performed using United States Environmental Protection Agency (USEPA) recommended Air Dispersion Modeling software. Monthly emissions data, terrain information and weather data were obtained and used to create a one year study of the dispersion of NOx and SOxs in the vicinity of the Refinery. Ambient air concentration contour maps for SOx and NOx were created to illustrate the dispersion of these pollutants on a monthly basis. Chronological NOx and SOx emissions were obtained indirectly from calculations based on first principle modeling and data from furnace and boiler online Oxygen analyzers and refinery fuel flow meters. Weather data were gathered from the refinery's local weather station and other weather data requirements such as mixing height and stability were calculated based on mathematical correlations. Terrain data from the refinery's pilot plan, aerial photographs, elevation contour maps and field survey were also incorporated into the model.